Radiographic and MRI characteristics of lumbar disseminated idiopathic spinal hyperostosis and spondylosis deformans in dogs. (12th April 2014) - Togni, A.; Kranenburg, H. J. C.; Morgan, J. P.; Steffen, F.
<x xml:space="preserve">Abstract</x> OBJECTIVES To evaluate clinical signs, describe lesions and differences in the magnetic resonance imaging appearance of spinal new bone formations classified as disseminated idiopathic spinal hyperostosis and/or spondylosis deformans on radiographs and compare degeneration status of the intervertebral discs using the Pfirrmann scale. METHODS Retrospective analysis of 18 dogs presented with spinal disorders using information from radiographic and magnetic resonance imaging examinations. RESULTS All dogs were found to be affected with both disseminated idiopathic spinal hyperostosis and spondylosis deformans. Neurological signs due to foraminal stenosis associated with disseminated idiopathic spinal hyperostosis were found in two dogs. Spondylosis deformans was associated with foraminal stenosis and/or disc protrusion in 15 cases. The Pfirrmann score on magnetic resonance imaging was significantly higher in spondylosis deformans compared with disseminated idiopathic spinal hyperostosis and signal intensity of new bone due to disseminated idiopathic spinal hyperostosis was significantly higher compared to spondylosis deformans. CLINICAL SIGNIFICANCE Differences between disseminated idiopathic spinal hyperostosis and spondylosis deformans found on magnetic resonance imaging contribute to an increased differentiation between the two entities. Clinically relevant lesions in association with disseminated idiopathic spinal hyperostosis were rare compared to those seen with spondylosis deformans.